Recurrent Vertebral Compression Fracture while on Bisphosphonate Therapy – What is the Next Best Step in Management? - Rianon, Nahid J.; Saraykar, Smita; Connoly, Fiona; Hnatow, Matthew; Ambrose, Catherine G. (International Journal of Orthopedics and Rehabilitation, 2015)
Bisphosphonates are widely used in the treatment of osteoporosis. They are highly effective in both increasing bone mass and preventing fractures in patients with osteoporosis. However, while osteoporosis treatment lowers the risk of fracture, almost half of the elderly suffer new fractures in their lifetime and many experience recurrent fractures during bisphosphonate therapy. Assessing the effectiveness of bisphosphonate therapy is problematic. Bone mineral density and markers of bone turnover are often used, but the true measure of effectiveness is prevention of new fractures. In this case report, we describe a severely osteoporotic patient who suffered a recurrent vertebral compression fracture during bisphosphonate therapy. In this case, bone turnover markers were markedly suppressed most likely as a result of bisphosphonate therapy or a combination of steroid and bisphosphonate therapy. As a result of the fracture, oral alendronate (a bisphosphonate) therapy was discontinued. We discuss the importance of understanding why some patients incur fractures while on bisphosphonate therapy and creating individualized treatment plans in these cases based on each patient’s physiology. Bisphosphonate therapy may suppress bone turnover, promote micro-fracture accumulation and facilitate development of recurrent fractures, particularly in patients taking glucocorticoids. Therefore, physicians should investigate the bone turnover rate for patients suffering a fracture while taking bisphosphonates, especially after a patient experiences recurrent fracture or is taking other medications known to adversely affect bone turnover. Furthermore, investigation of bone turnover prior to initiation of osteoporosis therapy, specifically after a recurrent fracture during bisphosphonate therapy, may provide additional, important information concerning the effectiveness of treatment options.